Elevated Detection of Dual Antibody B Cells Identifies Lupus Patients With B Cell-Reactive VH4-34 Autoantibodies - Peterson, Jacob N.; Boackle, Susan A.; Taitano, Sophina H.; Sang, Allison; Lang, Julie; Kelly, Margot; Rahkola, Jeremy T.; Miranda, Anjelica M.; Sheridan, Ryan M.; Thurman, Joshua M.; Rao, V. Koneti; Torres, Raul M.; et al. (Frontiers in Immunology, 2022)
About 5% of B cells in healthy mice and humans are allelically or isotypically included and hence co-express two different antibodies. In mice, dual antibody B cells (B2R) expand with systemic autoimmunity, co-express autoreactive and non-autoreactive antibodies, and participate in immune responses, but this phenomenon is strain dependent. This study was developed with two goals: 1) to establish the contribution of TLR and IFN receptor signaling to the development of germinal center B cells that express two antibodies in MRL/lpr mice; and 2) to determine whether B2R B cells are increased and particularly activated in a subset of adult patients diagnosed with systemic lupus erythematosus (SLE). Results from the MRL/lpr studies indicate that the enhanced differentiation of dual- B cells into germinal center B cells is due to a heightened response to TLR7 and TLR9 signaling, further fueled by an increased response to type II IFN. To understand the clinical and translational implications of our observations in mouse B2R B cells, cohorts of SLE patients and healthy controls were recruited and evaluated for expression of dual BCRs. Results from flow cytometry and microscopy revealed supraphysiological frequencies of k+l+ B2R cells in one fourth of the SLE patients. Abnormal numbers of k+l+ B cells correlated with higher frequencies of activated naïve B cells and age-associated B cells, and a lower proportion of “B cells that are naïve IgD+” (BND). However, results from single cell V(D)J sequencing demonstrated that these high k+l+ SLE patients harbored normal frequencies of k+l+ and other B2R B cells. and we further show that their B cells were instead decorated by k and l VH4-34 autoantibodies. Thus, our findings indicate that elevated flow cytometric detection of isotypically-included B cells can identify patients with high titers of B cell-reactive VH4-34 autoantibodies and abnormal distribution of B cell subsets relevant to autoimmunity.